Genetic variability for different quantitative characters in colocasia (Colocasia esculenta var. antiquorum.) - Padmakshi Thakur; Upendra Kumar Naik; Vikas Ramteke; Omesh Thakur (JOURNAL OF ROOT CROPS, 2023)
An experiment was conducted withnine Colocasia (Colocasia esculenta var. antiquorum (L.) Schott.) genotypes to evaluate the genetic variability for different quantitative characters. The experiment was conducted using a Randomized Complete Block Design with three replications. The genetic parameters between yield and yield contributing characters of different Colocasia genotypes were studied. Analysis of variance showed significant variation among the genotypes for all tested characters. The highest total yield was recorded in Indira Arvi-1 (29.54 t ha-1), which was followed by TTr 17-1 and TTr 17-12 (25.31 t ha-1 and 18.27 t ha-1, respectively). Corm weight showed the highest genotypic and phenotypic variance (71.52 and 72.41), whereas the number of leaves showed the lowest one (14.95 and 18.72). High value of heritability was observed for all the characters except number of leaves per plant. Genetic advance as percent of mean was reported highest for total yield, yield per plant, weight of cormels and plant height. The genotypes exhibited a wide range of variability for all the traits studied.